2017
DOI: 10.1088/1674-1056/26/5/057502
|View full text |Cite
|
Sign up to set email alerts
|

Influence of misch metal content on microstructure and magnetic properties of R–Fe–B magnets sintered by dual alloy method

Abstract: MM 14 Fe 79.9 B 6.1 /Nd 13.5 Fe 80.5 B 6 magnets were fabricated by dual alloy method (MM, misch metal). Some magnets have two Curie temperatures. Curie temperatures T c1 corresponds to the main phase which contains more LaCe, and T c1 decreases from 276.5 • C to 256.6 • C with the content of MM increasing from 30.3 at.% to 50.6 at.%. The variation of B r with the increase of MM indicates the existence of inter-grain exchange coupling in the magnets. When MM/R ≤ 30.3 at.%, the magnetic properties can reach the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The sharp decrease of (BH) max from 382.5 kJ/m 3 to 95.70 kJ/m 3 and the remarkable diminishment of H cj from 1219 kA/m to 111.8 kA/m are observed with increasing MM substitution from x = 0.0 to 1.0. The magnetic performance of x = 1.0 magnets is better than those reported in the literatures, [20,22,[25][26][27] as illustrated in Fig. 2.…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations
“…The sharp decrease of (BH) max from 382.5 kJ/m 3 to 95.70 kJ/m 3 and the remarkable diminishment of H cj from 1219 kA/m to 111.8 kA/m are observed with increasing MM substitution from x = 0.0 to 1.0. The magnetic performance of x = 1.0 magnets is better than those reported in the literatures, [20,22,[25][26][27] as illustrated in Fig. 2.…”
Section: Resultsmentioning
confidence: 66%
“…Figure 2 shows the comparison of (BH) max of [(Pr, Nd) 1−x MM x ] 13.8 Fe bal M 1.5 B 5.9 (x = 0.0, 0.5, 0.7, and 1.0) magnets with those of some MM based sintered magnets reported in the literatures. [20,22,[25][26][27][28][29] Generally, a dramatic drop of (BH) max occurs when x exceeds 0.5 for all the sintered magnets except the one fabricated by DMP process in this work. It is worthy to note, as mentioned previously, that the sintered magnets of x = 1.0, i.e., MM 13.8 Fe bal M 1.5 B 5.9 magnets in this work show the highest (BH) max to date, it is reasonable to conclude that the excellent magnetic performances of the sintered magnets by DMP process in this work probably could be attributed to the superior magnetic properties of the original alloy of MM 13.8 Fe bal M 1.5 B 5.9 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[1,2] In order to reduce the production costs more rationally and make rational use of rare earth resources, the partial substitution of misch-metal (MM) for Nd in Nd-Fe-B sintered magnets is thought to be an effective method to pursue high cost performance because of the inferior intrinsic properties and low cost of MM 2 Fe 14 B. [3][4][5][6] It has been found that the magnetic properties deteriorate drastically when Nd is replaced by Ce/La homogeneously in the 2:14:1 phase lattice. [5] Compared with the traditional single alloy method, the dual alloy method by mixing MM 2 Fe 14 B with Nd 2 Fe 14 B powders has an obvious advantage in preparing high abundant rare earth permanent magnets.…”
Section: Introductionmentioning
confidence: 99%